Gadolinium containing telechelic PEG‐polymers end‐capped by di‐phenylalanine motives as potential supramolecular MRI contrast agents. (15th November 2016) - Diaferia, Carlo; Gianolio, Eliana; Accardo, Antonella; Morelli, Giancarlo
Abstract : Telechelic PEG‐polymers end‐capped by diphenylalanine (FF) motives and containing a DOTA‐Gd complex, bound on a lysine side chain at the centre of peptide moiety, are studied for their assembling properties and for the relaxometric behavior. The observed variations in terms of relaxivity are correlated to the assembling properties of the aggregates by using several techniques: fluorescence, Circular Dichroism (CD) and Fourier Transform Infrared (FTIR) for aggregation tendency and secondary structure determination; Dynamic Light Scattering (DLS) and Transmission Electron Microscopy (TEM) for morphological definition. Self‐aggregation in water solution of the peptide conjugates, due to interaction of the phenylalanine frameworks, starts at concentration around 1 mg/ml with a first evidence of the coexistence of fibrillary networks and hydrogels at 10 mg/ml. Definitive presence of well‐structured fibrillary networks, dominated by an antiparallel β ‐sheet arrangement, occurs at 50 mg/ml. At the latter concentration relaxivity values measured at 20 MHz and 298 K, are around 11 mM −1  s −1, in line with a possible use of the these aggregates as MRI contrast agents. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Telechelic PEG‐polymers end‐capped by diphenylalanine (FF) motives as supramolecular T1‐contrast agents